METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK MENENTUKAN SISWA BERPRESTASI PADA MADRASAH ALIYAH NEGERI 16 JAKARTA - Rini Safitri; Jenie Sundari; Nila Hardi; Asep Sayfulloh (Just TI (Jurnal Sains Terapan Teknologi Informasi), 2023)
Being an outstanding student is every student's dream in school. The achievement obtained is certainly based on an ability to the knowledge possessed by each student. The criteria set in this case are test scores, extracurricular scores, attitudes, discipline and the number of attendances. For prospective students performing at the Aliyah Negri 6 Madrasah Jakarta are Bagas Satria, M. Salman, and Putri Larasati. Student selection is expected to make it easier for teachers to send prospective students and students for competitions and scholarships to students who have performed. The method used in this decision support system is AHP (Analytical Hierarchy Process) to help the selection of high achieving students. AHP method is a method whose main input is human perception. The AHP method can be used to determine high-achieving students with weights of 32% discipline, 24.2% attitude, 18.7% attendance, 14.3% exam scores, and 10.2% extracurricular scores. For candidates, Bagas Satria. has the highest priority weight of 0.45, M. Salman. has a second priority weight of 0.33 and Putri Larasati has a third priority weight of 0.19Keywords: Student Achievement Selection, Decision Support System, Analytical Hierarchy Process